SOSIALISASI HUKUM WARIS ISLAM DI DESA BANTAR JAYA GUNA MENCIPTAKAN KELUARGA SAKINAH - Indah Choiriyah Putri Hartono; Yoyo Hambali; Musyaffa Amin Ash Shabah (Al-Ihsan: Journal of Community Development in Islamic Studies, 2023)
Frequent disputes over the division of inheritance often lead to conflicts between households and relatives. This community service activity aims for a better understanding of the principles of inheritance law and creates an attitude of respect for family values to maintain good relationships within the family and respect the will of their parents or ancestors regarding inheritance. The service method applies community education in the form of socialisation. The results of the activity have an impact, namely, it can increase understanding and information about Islamic Inheritance Science to be applied in family life, can generate a sense of respect for family values to maintain good relationships in the family and respect the will of their parents or ancestors regarding inheritance and improve family communication.